(untitled) (Per Musi, 2021)
Music can become a tool for therapeutic change, per se or incorporated into other disciplines of Health Sciences. The objective of our study was the development of musical activities that could be relevant for the treatment of different ailments from Physiotherapy. The students, in the context of the subject "Music therapy", through role-playing, proposed different activities around which they reflected on their usefulness in the cases and professional fields proposed, with the intention of concluding their usefulness and applicability in Physiotherapy. The experts in Physiotherapy analyzed the results and showed their reviews for the best adaptation to the physiotherapy space. Experts and students agreed that certain concepts could be adapted to be used in Physiotherapy, thus instrumentalizing Music in and for said space, beyond its understanding as a background auditory element for relaxation.